2011
DOI: 10.1155/2011/528784
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Fusion Induced by Small Molecules and Ions

Abstract: Membrane fusion is a key event in many biological processes. These processes are controlled by various fusogenic agents of which proteins and peptides from the principal group. The fusion process is characterized by three major steps, namely, inter membrane contact, lipid mixing forming the intermediate step, pore opening and finally mixing of inner contents of the cells/vesicles. These steps are governed by energy barriers, which need to be overcome to complete fusion. Structural reorganization of big molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 123 publications
(150 reference statements)
2
58
0
Order By: Relevance
“…That is, there is slow transfer of lipids between the apposed bilayers but the aqueous interiors are not connected. This conclusion is not surprising for a couple of reasons; a) the liposomes are primarily comprised of POPC, a cylindrical polar lipid that is known to energetically favour a planar lamellar structure and disfavour the curved surfaces that are formed during the process of full membrane fusion, and b) the long PEG chains that project from the membrane exterior hinder close contact of the aggregated bilayers . Although full membrane fusion and aqueous content mixing is needed for effective cytosol delivery of polar payloads such as large macromolecules, selective targeting of stable liposomes to cell surfaces is also a desirable process for controlled delivery of lipophilic drugs and also for many imaging applications …”
Section: Resultsmentioning
confidence: 99%
“…That is, there is slow transfer of lipids between the apposed bilayers but the aqueous interiors are not connected. This conclusion is not surprising for a couple of reasons; a) the liposomes are primarily comprised of POPC, a cylindrical polar lipid that is known to energetically favour a planar lamellar structure and disfavour the curved surfaces that are formed during the process of full membrane fusion, and b) the long PEG chains that project from the membrane exterior hinder close contact of the aggregated bilayers . Although full membrane fusion and aqueous content mixing is needed for effective cytosol delivery of polar payloads such as large macromolecules, selective targeting of stable liposomes to cell surfaces is also a desirable process for controlled delivery of lipophilic drugs and also for many imaging applications …”
Section: Resultsmentioning
confidence: 99%
“…Exogenous surfactant-induced interfacial surface tension, i.e., "water stress," is the biophysical basis [1][2][3] for the generalized Sanarelli-Shwartzman phenomenon, generalized thrombohemorrhagic phenomena, the nonspecific generalized stress adaptation syndrome, the systemic inflammatory response syndrome, immune cell activation, macropinocytosis [73,[304][305][306], vesiculation [77], adhesion [63,64,78], engulfment [45,46,256], envelopment [309], fusion [74,77,78,172,[309][310][311], podokinesis [312][313][314][315], transcellular diapedesis [316] and nutritive endocytosis [317][318][319][320]. These highly-stereotyped supramolecular (mesoscopic), quantum coherent, biological processes are examples of the biophysical properties which motivate homeopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Esitashvili and Msuknishvili observed an increase in blood surface tension during acute myocardial infarction in humans [54]. Electrostatic interactions and interfacial charge regulation of biomembranes is a focus of intense ongoing research [65][66][67][73][74][75][76][77][78][79][80][81]. Fiszer-Kierzkowska recently suggested that cationic liposomes may not be suitable vehicles for gene transfection, given that they produced apoptosis and aggregation of misfolded proteins and/or fluidity changes of cellular membranes [82].…”
Section: Introductionmentioning
confidence: 99%
“…Besides these normal development‐associated and tightly regulated fusion processes, hybrid cell formation can also occur spontaneously by “accidental cell fusion” which is favorized by a fusion‐permissive environment including acidic pH, hypoxia, accumulation of damage‐associated molecular patterns, and membrane lipids destabilizing ions and peptides . Accordingly, cell fusion can generate aneuploidy, chromosomal instability, and DNA damage, all of which cause multiple genetic aberrations and potentially neoplastic development .…”
Section: Introductionmentioning
confidence: 99%